Fish species composition and morphological descriptions of five dominant families from inland waters of Kebbi state-Nigeria - Bawaa, D. Y.; S. M. Nurul Amin; Arshad, Aziz; Md Yusoff, Fatimah; Argungu, L. A. (Sciencedomain International, 2019)
A study was conducted on fish species composition and morphological features of five dominant fish families from the inland waters of Kebbi state, Nigeria between January and December 2017. Three major fishing communities (Argungu, Sabiyel and Yauri) were selected for the study. Fish samples were qualitatively collected from the commercial landings of the fishermen using gill nets. The analysis of the distribution of fish species were analyzed using Microsoft Excel software In total 18 fish species belonging to 10 families were identified from the inland waters of Kebbi state. Viz: Bagridae, Cichlidae, Claridae, Mormyridae, Citharacidae, Characidae, Mochokidae, Melaptaruridae, Schilbeidae and Cyprinidae. Among the 10 identified families, Bagridae (22.22%) and Mormyridae (16.66%) which accounted for four and three species respectively, were the most dominant families.